2022
DOI: 10.31234/osf.io/6eszj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The alarms should no longer be ignored: A Survey of the Demand, Capacity and Provision of Adult Community Eating Disorder Services in England and Scotland before COVID-19

Abstract: Aims and Methods: This national survey compared the demand and capacity of adult community eating disorder services (ACEDS) to NHSE Commissioning guidance. Results: Of 21 services approached in England and Scotland 13 responded (10.7 million total population). Between 2016/17 and 2019/20, the average referral rate increased by 18.8%, from 378 to 449/million population. Only 3.7% of referrals were from child and adolescent eating disorder services (CEDS-CYP), yet 46% of referrals were 18-25 years old.Most ACEDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The specific systemic challenges encountered in the DAISIES trial demonstrate the profound impacts of an underfunded and overburdened system on research implementation, underscoring the need for investment into adult ED services in the UK as has previously been suggested regarding improving care (Viljoen et al, 2022). The results suggest that currently, conducting an RCT of the scope and magnitude of the DAISIES trial may not be possible within intensive adult ED services in the UK, and alternative research designs should be explored, such as naturalistic longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…The specific systemic challenges encountered in the DAISIES trial demonstrate the profound impacts of an underfunded and overburdened system on research implementation, underscoring the need for investment into adult ED services in the UK as has previously been suggested regarding improving care (Viljoen et al, 2022). The results suggest that currently, conducting an RCT of the scope and magnitude of the DAISIES trial may not be possible within intensive adult ED services in the UK, and alternative research designs should be explored, such as naturalistic longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…While our paper adds to this growing literature and could address high rates of relapse by focusing on the underlying emotion di culties which precede and maintain ED thoughts and behaviours (Henderson et al, 2021;Treasure et al, 2012;Warne et al, 2023), it also suggests that psychoeducation about emotions can be successfully conducted online in a cost-effective way. In the UK, demand for treatment far outstrips the capacity of adult ED services (Striegel Weissman & Rosselli, 2017; Viljoen et al, 2022). This leaves the majority of individuals with EDs to suffer long waiting times (Austin et al, 2021), which translate into worsening of symptoms (Vollert et al, 2019), higher total healthcare costs (Bothe et al, 2022), lower treatment uptake (Flynn et al, 2021), and less likelihood of responding positively to treatment (Austin et al, 2021;Fernández-Aranda et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In our own study, more than 30% of our former inpatients who had suffered from AN needed further support from an AED service (Herpertz‐Dahlmann & Gilsbach, 2022). As AEDS are usually much larger than CAEDS, these cases make up a much smaller percentage of referrals to adult services: A study of 13 AED services in the UK found that only about 4% of referrals were transitions from CAEDS even though nearly 50% of their referrals were emerging adults (age 18–25) (Viljoen et al., 2022).…”
Section: How Many Patients Need a Transition From A Childhood Eating ...mentioning
confidence: 99%
“…In some countries, such as the UK, AEDS are substantially less well funded than CAEDS and therefore will not have the capacity to deliver treatments of similar intensity and in a timely fashion (Viljoen et al., 2022).…”
Section: Which Factors Constitute the Most Important Challenges For T...mentioning
confidence: 99%
See 1 more Smart Citation